Target Localization by Resolving the Time Synchronization Problem in Bistatic Radar Systems Using Space Fast-Time Adaptive Processor. (3rd February 2009) - Madurasinghe Madurasinghe, D. D.; Shaw Shaw, A. P. A. P.
Abstract : The proposed technique allows the radar receiver to accurately estimate the range of a large number of targets using a transmitter of opportunity as long as the location of the transmitter is known. The technique does not depend on the use of communication satellites or GPS systems, instead it relies on the availability of the direct transmit copy of the signal from the transmitter and the reflected paths off the various targets. An array-based space-fast time adaptive processor is implemented in order to estimate the path difference between the direct signal and the delayed signal, which bounces off the target. This procedure allows us to estimate the target distance as well as bearing.